If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 5b + -6 = -10 Reorder the terms: -4 + -6 + 5b = -10 Combine like terms: -4 + -6 = -10 -10 + 5b = -10 Add '10' to each side of the equation. -10 + 10 + 5b = -10 + 10 Combine like terms: -10 + 10 = 0 0 + 5b = -10 + 10 5b = -10 + 10 Combine like terms: -10 + 10 = 0 5b = 0 Solving 5b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '5'. b = 0 Simplifying b = 0
| X*4-61=x*2-13 | | x^3+3x^2y+3xy^2+y^3=-64 | | s(23)=9t-4 | | 3x-2-x^3=0 | | 325-135-89=c | | 8k+3k-4k=56 | | x^3+3x^2y+3xy^2+y^3+64=0 | | v=p*r^2*h | | x^2+6x+14=-6x+3 | | 135+89=325c | | 25x^3=49x | | 2a+18= | | 135+89c=325 | | 6=1x+6x-1 | | y=-6+-2x | | m^3+4m^2+5m+2=0 | | sin(4x)-sinx= | | x^2-9=(x-3)(4x+6) | | -6-3y=18 | | 2(6x+15)+2(7x+7)=360 | | 2x^2-36-6x=0 | | 54-3x=11-10x | | 9(x+3)=5(x+11) | | t=2m-v | | 5x^2+10x+15=18 | | -1x-6x=9-8x | | 10x+8y*2x= | | 6+5x+4=15 | | 4y+1=22 | | 9x+10=-53 | | (2b+4)(b-3)=600 | | 3+3n-2n=4 |